2011
DOI: 10.1590/s0104-66322011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling and microbial assessment by fluorescent in situ hybridization in anaerobic sequencing batch biofilm reactors treating sulfate-rich wastewater

Abstract: -This paper reports the results of applying anaerobic sequencing batch biofilm reactors (AnSBBR) for treating sulfate-rich wastewater. The reactor was filled with polyurethane foam matrices or with eucalyptus charcoal, used as the support for biomass attachment. Synthetic wastewater was prepared with two ratios between chemical oxygen demand (COD) and sulfate concentration (COD/SO 4 2-) of 0.4 and 3.2. For a COD/SO 4 2-ratio of 3.2, the AnSBBR performance was influenced by the support material used; the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
(20 reference statements)
0
11
0
1
Order By: Relevance
“…Previous studies had reported COD/SO 4 2-ratios ranging from 6.6 to 1.7 as optimal for CODr (Choi and Rim, 1991;Friedl et al, 2009;Mockaitis et al, 2010;Silva et al, 2011;Camiloti et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies had reported COD/SO 4 2-ratios ranging from 6.6 to 1.7 as optimal for CODr (Choi and Rim, 1991;Friedl et al, 2009;Mockaitis et al, 2010;Silva et al, 2011;Camiloti et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…However, there was no significant difference of sulfide removal between 0 rpm and 100 rpm of agitation where the sulfide removal achieved 99.3% and 99% at 0 rpm and 100 rpm, respectively. The difference of sulfide removal at both agitation rate maybe due to the sensitivity of the microbes to the agitation where the agitation reduced the performance of the microbes in AS and reduced the sulfide removal [9]. Figure 2b showed that sulfide removal was increased proportionally to WW/AS ratio where sulfide removal achieved 99.4% at 3:1 ratio and 99.2% at 1:1 ratio.…”
Section: Effect Of Independent Processing Parameters On Sulfide Removmentioning
confidence: 97%
“…At 100 rpm of agitation sulfide removal decreased when the temperature increased. The sulfide removal decreased with agitation because the microbes were sensitive to the presence of agitation and reduced the performance of the microbes in the wastewater [9]. Figure 3d showed the interaction effect between HRT and different WW/AS ratios on sulfide removal.…”
Section: Effect Of Independent Processing Parameters On Sulfide Removmentioning
confidence: 99%
“…As this configuration presented good results treating synthetic wastewaters (removal efficiency up to 86%), the AnSBBR started to be studied and developed (Ratusznei et al, 2003;Rodrigues et al, 2003;Cubas et al, 2004;Pinho et al, 2004;Siman et al, 2004;Bezerra et al, 2010;Costabile et al, 2010). The AnSBBR was also tested and optimized with many types of wastewaters, including diluted whey (Damasceno et al, 2007), sewage (Sarti et al, 2007) wastewater of the personal-care industry (Oliveira et al, 2009), biodiesel production effluent (Selma et al, 2010;Bezerra et al, 2010), sucrose-based wastewater (Manssouri et al 2013) among other studies for optimization and improvement of the AnSBBR Silva et al, 2011;Vich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%